The Pathway of Black Swan: Violence and Construction of the Subject - Gómez Cardeña, Sophia (2019)
The aim of this paper is to analyze the film Black Swan (2011), directed by Darren Aronofsky, in order to understand the identity construction of a subject crossed by multiple violence: Nina, the ballet dancer. For this purpose, the analysis will focus on the relationship of the following concepts: the processes of recognition, the dynamics of power and violence, and the experience of motherhood. It is concluded that Nina’s character suffers a double violence. The first one is linked to a patriarchal scheme of structural violence towards women and the feminine and the second one is related to an intimate and symbolic violence: the fusion and lack of recognition of her as a human being separated from her mother.